Blanket wire utilizing positive temperature coefficient resistance heater - CROWLEY; GEORGE C (1982)
A heating element for use in an electric blanket or the like including conductors spaced apart in a positive temperature coefficient (PTC) material which serves as a self-limiting heater. The conductors are separated by a spacer which prevents the conductors from engaging each other when the PTC material softens or melts during annealing thereof. A coating of material having a higher melting point than the PTC material is placed over the PTC material to maintain its shape during the annealing process.